Case report: Unusual persistent hypotension and acute occlusion after peripheral paclitaxel balloon angioplasty - Yang, Lin; Liu, Jianlin; Liu, Chao (Frontiers in Cardiovascular Medicine, 2022)
Background Paclitaxel-coated balloon (PCB) angioplasty is a mainstream treatment for peripheral artery disease; however, the safety of PCB remains controversial. Case presentation We confirmed acute occlusion during PCB angioplasty in a patient with femoropopliteal artery occlusion. The occluded vessels were revascularized completely after endovascular medical therapy and bailout stenting angioplasty. Then, the patient experienced persistent post-procedure orthostatic hypotension (30 days) and received hydration and vasoactive agents with a target mean arterial blood pressure of 75–85 mmHg. The patient's blood pressure gradually recovered over the 30 days after the procedure, and there was no recurrence of symptomatic hypotension during the follow-up. Conclusions This rare complication is helpful to evaluate the safety of the PCB device.